An automated device for training white‐tailed deer to visual stimuli - Bradley S. Cohen; David A. Osborn; George R. Gallagher; Robert J. Warren; Karl V. Miller (Wildlife Society Bulletin)
Abstract Although many aspects of white‐tailed deer (Odocoileus virginianus) biology and physiology have been studied thoroughly, few studies have confirmed deer cognitive perception, partly because of the difficulty of efficiently training sufficient numbers of deer to respond behaviorally in controlled experiments. We present a system that trains white‐tailed deer to associate a supra‐threshold, white‐light stimulus with a food reward through operant conditioning techniques. The “deer training apparatus” (DTA) automatically dispenses food, rings a start buzzer, randomly assigns a stimulus light over 1 of 2 troughs, and registers a deer's choice. If a deer goes to a trough with the light illuminated, then a correct choice is registered. All 6 deer tested met successful training criteria by Day 19, and a performance of 88.2% ± 3.9% correct choices by Day 25. We conclude that the DTA presents an effective and efficient way of training white‐tailed deer, and provides an experimental platform for future research on behavior, perception, and preference. Thus, the DTA should be useful to researchers evaluating behavioral response of deer, and possibly other wild and domestic species, to various visual and auditory stimuli. © 2012 The Wildlife Society.